2005
DOI: 10.1177/147470490500300109
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Approach to Positive Emotion: Flowers

Abstract: For more than 5000 years, people have cultivated flowers although there is no known reward for this costly behavior. In three different studies we show that flowers are a powerful positive emotion "inducer". In Study 1, flowers, upon presentation to women, always elicited the Duchenne or true smile. Women who received flowers reported more positive moods 3 days later. In Study 2, a flower given to men or women in an elevator elicited more positive social behavior than other stimuli. In Study 3, flowers present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(80 citation statements)
references
References 57 publications
4
70
0
2
Order By: Relevance
“…This is confirmed in the above described empirical research that shows that flowers enhance receptivity to romantic request in Western cultures [31]. Similarly, Haviland Jones and colleagues have found that flowers enhance women's positive emotions and social behavior [2].…”
Section: Introduction and Literature Surveysupporting
confidence: 68%
See 2 more Smart Citations
“…This is confirmed in the above described empirical research that shows that flowers enhance receptivity to romantic request in Western cultures [31]. Similarly, Haviland Jones and colleagues have found that flowers enhance women's positive emotions and social behavior [2].…”
Section: Introduction and Literature Surveysupporting
confidence: 68%
“…We can assume that if flowers induce such positive emotion and if positive emotion is so central to human emotional needs, then this is the incentive of humans to culture flowers [2]. Humans are also embedded in a larger sensory and social environment than that occupied by their own species [11].…”
Section: Introduction and Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the mere perception of beautiful, or sweet and energy-rich objects seems to trigger pleasure (Kahneman et al, 1997). As such, humans may enjoy furnishing their living environment with flowers (Haviland-Jones, Rosario, Wilson, & McGuire, 2005) or being immersed in nature, such as a lush meadow or forest, particularly when feeling exhausted (Kaplan, 1995). Likewise, users appear to enjoy perceiving supportive environments portrayed by the media, particularly if they undergo depleting life episodes (Katz & Foulkes, 1962).…”
Section: The Enjoyment Of Recreation and Psychological Growthmentioning
confidence: 99%
“…The widespread social norm of giving flowers to others is also suggestive of nature's ability to foster positive relations. Indeed, evidence from experimental studies demonstrates that participants primed with flowers are more likely to help strangers (Guéguen, Meineri, & Stefan, 2012), give money to others (Raihani & Bshary, 2012;Stillman & Hensley, 1980), act gregariously (Haviland-Jones, Rosario, Wilson, & McGuire, 2005), and feel attracted to someone they have just met (Guéguen, 2011(Guéguen, , 2012. Trait nature connectedness is positively associated with humanitarianism (Nisbet et al, 2009), social wellbeing (Howell, Dopko, Passmore, & Buro, 2011;Howell, Passmore, & Buro, 2013), kindness (Leary et al, 2008), empathic concern (Zhang, Piff, Iyer, Koleva, & Keltner, 2014), altruistic concern (Schultz, 2001), and perspective taking (Schultz, 2001).…”
Section: Nature and Eudaimonic Wellbeingmentioning
confidence: 99%